REACHING NEW HEIGHTS: KEVIN GILL '11G, Computer Science. - Agresto, Julia (InSight: Rivier Academic Journal)
The article features Kevin Gill, a software engineer and developer and a 2011 graduate of Rivier University's Master of Science in Computer Science programs. He became famous after he developed a software that generates a set of hypothetical images that portray Mars as a living, vibrant planet. He claims that his skills were developed with the help of his teachers, including Dr. Vladimir Riabov.